Miftah Ismail’s The One Per Cent Republic: A Critical Discourse Analysis - Saqlain Shah; Duaa Memon (University of Chitral Journal of Linguistics and Literature, 2023)
This paper applies Critical Discourse Analysis (CDA) using Fairclough’s three-dimensional model to analyze Miftah Ismail’s article The One Per Cent Republic published in Daily Dawn Newspaper. Ismail is a prominent political economist of Pakistan. He asserts that under the Islamic Republic of Pakistan, only the top one per cent of the country’s people have access to resources, wealth, and opportunity, hence the country should rather be called as the One Per Cent Republic. This study aims to understand the critique of the power structure, socioeconomic disparity, wealth concentration, colonial linguistic divide, elitist education, family influence, exclusive health facilities, and social mobility in Pakistan, as expressed by Ismail. Ismail finds this elite capture as the root cause behind Pakistan’s economic, political, and social issues; he therefore calls all the stakeholders of the nation to sit and create a new social contract based on inclusiveness of all social strata and viable for the country’s growth and sustainable human development.